2017
DOI: 10.3389/fnins.2017.00659
|View full text |Cite
|
Sign up to set email alerts
|

A Sub-millimeter, Inductively Powered Neural Stimulator

Abstract: Wireless neural stimulators are being developed to address problems associated with traditional lead-based implants. However, designing wireless stimulators on the sub-millimeter scale (<1 mm3) is challenging. As device size shrinks, it becomes difficult to deliver sufficient wireless power to operate the device. Here, we present a sub-millimeter, inductively powered neural stimulator consisting only of a coil to receive power, a capacitor to tune the resonant frequency of the receiver, and a diode to rectify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 40 publications
1
58
0
Order By: Relevance
“…It has approximate dimensions of 2×0.5×0.5 mm, and operates by rectifying induced voltages at a predetermined resonance frequency (e.g. 10 MHz) to produce a DC electric field capable of depolarizing adjacent neurons (Freeman et al 2017). Like TMS, this device relies on external application of magnetic fields, but in this case the field is used solely as a source of wireless power for an electrical device.…”
Section: Inductive Methodsmentioning
confidence: 99%
“…It has approximate dimensions of 2×0.5×0.5 mm, and operates by rectifying induced voltages at a predetermined resonance frequency (e.g. 10 MHz) to produce a DC electric field capable of depolarizing adjacent neurons (Freeman et al 2017). Like TMS, this device relies on external application of magnetic fields, but in this case the field is used solely as a source of wireless power for an electrical device.…”
Section: Inductive Methodsmentioning
confidence: 99%
“…1, Methods). In experiments using ME films and Pt electrodes we found that high-frequency biphasic stimulation at the ME resonance frequency (typically 20-150 kHz) was not effective to stimulate APs in cultured HEKs, as predicted by the low-pass filtering properties of the cell membrane (Freeman et al 2017). To create an effective monophasic stimulus waveform, we used a Schottky diode to rectify the voltage to create entirely positive or negative voltage waveforms depending on the diode direction.…”
Section: Monophasic Stimulation By Me Films Modulates Cellular Activimentioning
confidence: 99%
“…Thus, when the receiver coils are miniaturized, the output power reduces and becomes more sensitive to perturbations in the distance or angle between the transmitter and receiver (Fotopoulou & Flynn 2011). For example, Freeman et al demonstrated that small inductive coils less than 1 mm in diameter can power stimulators for the sciatic nerve in anesthetized rats (Freeman et al 2017); however, the stimulation frequencies have been limited to less than 50 Hz and stable performance has been difficult to achieve in freely moving animals due to the reduced power coupling efficiency that accompanies changes in the angle and distance between the receiver and transmitter during behavior (Maeng et al 2019). Near-field inductive coupling has also been used to power optogenetic stimulators in freely moving mice (Shin et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional constant-current stimulators can be implemented in a small area using integrated circuit technology, yet dissipate substantial power across the current source itself when powered by a DC supply voltage. Recently developed millimeter-sized stimulation systems [25], [33], [34] were implemented with off-the-shelf discrete components so that their power efficiencies were compromised with simplicity in implementation. On the contrary, adiabatic stimulators, which slowly ramp the supply voltage up and down to minimize the voltage drop across the current source and recycle charge from electrode and tissue capacitance as described in Section II-C, can be more energy efficient, yet typically require large off-chip passives to synthesize the adiabatic voltage waveforms [28], [35].…”
Section: Introductionmentioning
confidence: 99%
“…This is typically accomplished in wirelessly-powered systems via a two-step rectification/boosting (and/or regulation) process that introduces cascaded losses and further degrades efficiency. As nextgeneration neural stimulation devices continue to shrink in size [25], [33], [34], [36], in some cases via full on-chip integration of all necessary neuroinstrumentation functionality [37], [38], inclusion of energy-efficient adiabatic stimulation functionality is necessary in a small, fully-integrated form factor. This paper presents an adiabatic current-controlled stimulator architecture, depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%